Valorization of cultural diversity throught Good Practices Dissemination on Art Mediation: sharing experiencies - Dimitrina J. Semova (Arteterapia)
In this article, as part of the Erasmus+ project “Divercity”, we focus on the collection and analysis of good practices in Spain and other countries in Europe. The project revolves around the development of methods that valorize cultural diversity and in this respect, identifying and sharing best practices on diversity and inclusion through artistic mediation inside museums, culture institutions, our urban walks, forms an mandatory stage of the research process.